The inclusion of aviation in the European Emission Trading Scheme. - Schade, Vincent (Diplomica Verlag, 2014)
A significant volume of literature already exists concerning the inclusion of aviation in the EU-ETS. Most of the research laid its focus on specific industry levels such as the individual airline, the aviation industry in general or macroeconomic aspects. In this context, these studies tried to anticipate market reactions triggered by the EU-ETS by analyzing specific issues such as the financial impact on airlines, changes in competitive behavior or implications for the overall industry development. As a consequence, the existing studies took only a limited market view and made assumptions ab.